(untitled) (Research, Society and Development, 2022)
Objective: To describe and discuss the number of hospital admissions for diarrhea and gastroenteritis of infectious origin in children aged 0 to 4 years in Macaé/RJ, compared to the State of Rio de Janeiro and Brazil. Methodology: Epidemiological research with a quantitative approach with retrospective analysis based on secondary data. Data collection took place between July 2020 and May 2021, analyzing the period from 2016 to 2020. Results: In the city of Macaé in 2016, 4 children were hospitalized for some diarrheal disease and gastroenteritis of infectious origin; 6 children in 2017; 4 children in 2018; 3 children in 2019 and 2 children in 2020. In the state of Rio de Janeiro in 2016, 1,046 children were hospitalized for some diarrheal disease and gastroenteritis of infectious origin; 959 children in 2017; 1,176 children in 2018; 1,362 children in 2019 and 1,427 children in 2020. In Brazil, in 2016, 45,239 children were hospitalized for some diarrheal disease and gastroenteritis of infectious origin; 34,940 children in 2017; 33,499 children in 2018; 31,777 children in 2019 and 18,234 children in 2020. Conclusion: On public information platforms on child morbidity and mortality, Macaé showed large differences in child hospitalization patterns compared to state and national data that show significant numbers of children falling ill from this preventable cause. Thus, it is necessary to expand investigations with regard to childhood hospitalizations for diarrhea and gastroenteritis of infectious origin.